Neuroendocrine cells of the prostate: Histology, biological functions, and molecular mechanisms - Butler, William (Precis Clin Med, 2021)
Prostate cancer (PCa) is a common cause of cancer-related mortality in men worldwide. Although most men are diagnosed with low grade, indolent tumors that are potentially curable, a significant subset develops advanced disease where hormone therapy is required to target the androgen receptor (AR). Despite its initial effect, hormone therapy eventually fails and the tumor progresses to lethal stages even through continued inhibition of AR. This review article focuses on the role of PCa cellular heterogeneity in therapy resistance and disease progression. Although AR-positive luminal-type cells represent the vast majority of PCa cells, there exists a minor component of AR-negative neuroendocrine (NE) cells that are resistant to hormonal therapy and are enriched by the treatment. In addition, it is now well accepted that a significant subset of hormonally treated tumors recur as small cell neuroendocrine carcinoma (SCNC), further highlighting the importance of targeting NE cells in addition to the more abundant luminal-type cancer cells. Although it has been long recognized that NE cells are present in PCa, their underlying function in benign prostate and molecular mechanisms contributing to PCa progression remains poorly understood. In this article, we review the morphology and function of NE cells in benign prostate and PCa as well as underlying molecular mechanisms. In addition, we review the major reported mechanisms for transformation from common adenocarcinoma histology to the highly lethal SCNC, a significant clinical challenge in the management of advanced PCa.